THE FEMININE SOCIAL ROLE IN THE SHORT STORY “A FUGA”, BY CLARICE LISPECTOR (Muitas Vozes, 2021)
This article aims to analyze the short story “A fuga”, by Clarice Lispector, published in 1940, in order to discuss aspects related to the feminine role, represented by the protagonist Elvira. It also seeks to situate the literary production of author in the context of the 1940s, period when regionalist narratives prevailed, figuring aspects of the national reality. Regarding the results obtained with the present analysis, based on studies by Brasil (1969), Candido (1970; 1987), Süssekind (1987), Nunes (1989), Santiago (1999), Bourdieu (2012), Bosi (2015), Zolin (2015), among others, it is possible to verify that the author, besides presenting a narrative and esthetic model dissonant of the fiction of 1940, fracturing with the commitment to present the Brazilian reality, also reveals the feminine social reality, promote a critique of patriarchal values and dominant gender patterns.